Implementação das boas práticas de fabricação na Agroindústria Doce Coperjaíba - Bianca Mesquita Pereira Garcez (2023)
Diseases transmitted by contaminated food (DTAs), considered a global public health concern, require relevance in their approach in the areas of food production and processing, due to their interaction with food safety and preservation of consumers' health. Good Manufacturing Practices are guidelines established by Brazilian legislation that food processing companies and service providers in the area must follow to contribute to ensuring the quality of the food produced. In view of this, this work aimed to monitor the production of banana and guava sweets from Agroindústria Doce CoperJaíba and, based on the habits and routines identified by the application of the Good Manufacturing Practices Checklist established by RDC nº 275 of 2002, preparing the Good Manufacturing Practices Manual and developing and applying the Good Manufacturing Practices Training for food handlers. From the results of the study, there was a general classification of the company's classification in Group II (51 to 75% of compliance with the items), as it obtained 59.3% of conformity of the items evaluated according to the Checklist of the referred legislation. The percentages of compliance with the requirements within the five blocks described in the Checklist were: Equipment and Utensils (78.9%), Food Production and Transport (77.8%), Buildings and Installations (68.7% ), Handlers (28.6%) and Documentation (0%). In view of the results, after preparing and executing a plan to correct non-conformities in the worst performing blocks, the Good Practices Manual was prepared and then Good Manufacturing Practices Training was given to handlers. With this research, it was possible to conclude that the Checklist of RDC 275/2002 proved to be effective in obtaining the hygienic and sanitary diagnosis of the agroindustry routines, as well as in directing the actions adopted for the implementation of the company's good manufacturing practices.